IMPLEMENTATION OF REMEDIAL TEACHING IN IMPROVING ISLAMIC EDUCATION LEARNING ACHIEVEMENT - Nurhasanah, Nurhasanah (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
The learning process is a very important issue in the educational process. In the learning process activities there are interactions or reciprocal relationships between teachers and students. The activity will take place in an educative situation in order to achieve the set goals. In the implementation of learning will be able to know the results obtained by students. If the results do not reach the Teaching Completeness Criteria (KKM), then a remedial is needed, both remedial teaching and remedial learning. In this article, we will discuss Remedial Teaching in order to give good hope to students who experience learning difficulties. If these learning difficulties are not taken seriously, failure will be experienced forever. The concept of remedial teaching has actually been introduced for a long time, especially in relation to evaluation of learning outcomes. However, explanations regarding remedial teaching were carried out in a vague manner and did not receive proper portion. Perhaps this is one of the reasons why remedial teaching gets less attention from teachers, so it is only natural that remedial teaching does not develop rapidly in school classes. Remedial Teaching which is applied to PAI learning has the goal of being able to correct the deficiencies of each individual student's different achievements. In addition, another goal is to provide assistance in overcoming the learning lag of students who are slow and have difficulty accepting PAI lessons so that they are able to absorb PAI subject matter on an equal footing with their other friends.